Nouvelles données sur la datation des dépôts miocènes de l’Algarve (Portugal), et l’évolution géologique regionale - Antunes, M. Telles; Bizon, G.; Nascimento, A.; Pais, João (2008)
This paper presents a resume of the results achieved by researchers of the Centro de Estratigrafia e Paleobiologia da U. N. L. on the Neogene of Algarve, since 1977. The detailed study of several profiles as well as that af calcareous nannoplanton, planktonic foraminifera, ostracoda, fishes and mammals allowed to obtain data and correlation elements leading to a new interpretation of the Miocene of Algarve. It was possible to date and to characterize the following units: a) Carbonate formation of Lagos-Portimão, of marine facies, ascribed to the Lower Miocene (Aquitanian? and mainly Burdigalian), possibly attaining the Lower Langhian. b) Essentially arenaceous series of continental facies with a marine intercalation of Arrifão, Olhos de Água and Auramar Hotel beach, middle Miocene (Langhian-Serravallian) in age. c) Marine (tripoli, conglomerates, sands and limestones) deposits of Tunes-Mem Moniz, Ponte das Lavadeiras (Faro), Arroteia (Fuzeta) and Luz de Tavira, corresponding, at least partially, to the first part of the upper Miocene (Lower Tortonian). d) Cacela formation with three members: The lower member (conglomerates and sands), the middle (yellow silts) and the upper ones (gray silts), uppermost Tortonian and mainly Messinian in age. An interpretation of the tectonic and paleogeographic evolution of the portuguese littoral during the Miocene is also presented considering its insertion in the meridional part of the Peninsula (Guadalquivir depression, Betic massif basins and in the spanish Levant in general). Comparisons among the Neogene vulcanism of this region and similar manifestations documented in Algarve (basanite of Figueira-Portimão, etc) are established.